\begin{tabular}{l} Question 8 \\ Solve for \( x x^{2} \) \\ \( 7-\frac{18}{(6 x+4)^{-13}}+6=27 \) \\ Round to 3 decimal places \\ Rod your answer \\ \hline\end{tabular}
Solución de tutoría real
Responder
Solución
Revisado y aprobado por el equipo de tutoría de UpStudy
Bonus Knowledge
To solve for \( x x^{2} \) in the equation \( 7 - \frac{18}{(6x + 4)^{-13}} + 6 = 27 \), we first simplify the equation: 1. Combine like terms on the left: \( 13 - \frac{18}{(6x + 4)^{-13}} = 27 \). 2. Rearrange to isolate the fractional term: \(-\frac{18}{(6x + 4)^{-13}} = 27 - 13\) \(-\frac{18}{(6x + 4)^{-13}} = 14\). 3. Multiply both sides by \(-1\): \(\frac{18}{(6x + 4)^{-13}} = -14\). 4. To eliminate the fraction, multiply both sides by \((6x + 4)^{-13}\): \(18 = -14(6x + 4)^{-13}\). 5. Rearranging gives: \( (6x + 4)^{-13} = -\frac{18}{14} = -\frac{9}{7} \). This result indicates we have an error since the left-hand side cannot be negative. Let’s try solving it step-by-step instead: From our corrected approach, we re-solve to find \( x \): 1. Set up \( 7 + 6 - 27 = \frac{18}{(6x + 4)^{-13}} \). 2. Simplifying gives \( -14 = \frac{18}{(6x + 4)^{-13}} \). 3. Since \(-14\) is negative as mentioned, you typically avoid non-reality. Thus instead of a numerical evaluation, it seems there's a conceptual block needing clarification or re-writing the parameters provided. Therefore, recheck the equation for any omissions or ask for further insights to visualize the setups correctly for \(x\). Exploring alternative equations or interpretations can become handy too!